PENINGKATAN HASIL BELAJAR IPS SISWA KELAS IV SDN 167 PEKANBARU MELALUI PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Sentosa, Fedrik; Witri, Gustimal; Noviana, Eddy (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2020)
This study was based on the low learning outcomes of social studies in fourth grade students at SDN 167 Pekanbaru. To overcome this learning problem, classroom action research is carried out by applying the contextual teaching and learning (CTL) approach. The purpose of this study is to improve social studies learning outcomes by applying the CTL approach. This research is a classroom action research conducted in the fourth grade SDN 167 Pekanbaru with a total of 20 students. This research was conducted in two cycles, the data collection techniques used were observation and written tests. The analysis technique used is descriptive analysis of data on teacher and student activities and social studies learning outcomes. The results of the study state that the application of the CTL approach can improve the activities of teachers and students as well as social studies learning outcomes.